CHANGES IN THE SECONDARY STRUCTURE AND ASSEMBLY OF PROTEINS ON FLUORIDE CERAMIC (CEF3) NANOPARTICLE SURFACES - Sakaguchi, Naoya; Kaumbekova, Samal; Itano, Ryodai; Torkmahalleh, Mehdi Amouei; Shah, Dhawal; Umezawa, Masakazu (ACS Applied Bio Materials, 2022)
Fluoride nanoparticles (NPs) are materials utilized in the biomedical field for applications including imaging of the brain. Their interactions with biological systems and molecules are being investigated, but the mechanism underlying these interactions remains unclear. We focused on possible changes in the secondary structure and aggregation state of proteins on the surface of NPs and investigated the principle underlying the changes using the amyloid β peptide (Aβ16−20) based on infrared spectrometry. CeF3 NPs (diameter 80 nm) were synthesized via thermal decomposition. Infrared spectrometry showed that the presence of CeF3 NPs promotes the formation of the β-sheet structure of Aβ16−20. This phenomenon was attributed to the hydrophobic interaction between NPs and Aβ peptides in aqueous environments, which causes the Aβ peptides to approach each other on the NP surface and form ordered hydrogen bonds. Because of the coexisting salts on the secondary structure and assembly of Aβ peptides, the formation of the β-sheet structure of Aβ peptides on the NP surface was suppressed in the presence of NH4 + and NO3 − ions, suggesting the possibility that Aβ peptides were adsorbed and bound to the NP surface. The formation of the β-sheet structure of Aβ peptides was promoted in the presence of NH4 + , whereas it was suppressed in the presence of NO3 − because of the electrostatic interaction between the lysine residue of the Aβ peptide and the ions. Our findings will contribute to comparative studies on the effect of different NPs with different physicochemical properties on the molecular state of proteins.
Keywords: Type of access: Open Access; amyloid β peptide; fluoride nanoparticles; infrared spectrometry; molecular dynamics; β-sheet